Life after the virus : social reproduction in a post pandemic world - Féliz, Mariano (2020)
The COVID-19 pandemic is not just another health or economic crisis. It is fundamentally a crisis of social reproduction and care work. Hospitals and care facilities are being pushed to the brink by those affected by the virus. Reproductive work in homes and communities is being stretched to its limits, with women once again carrying the load. In dependent territories and in the peripheries of big cities around the world, community networks for the provision of water, food, childcare and other basic needs are being put to the test, often overrun with millions at risk. What is at stake now is how we take care of each other and how we attend to the fact that we are fragile beings. Life on the planet as we know it is on the brink of radical transformation. Rosa Luxemburg?s question still applies: will we turn this into a time for revolution, or will we be unable to stop it from falling into a new barbarism?